2021
DOI: 10.1111/pim.12882
|View full text |Cite
|
Sign up to set email alerts
|

A 250‐kDa glycoprotein of Naegleria fowleri induces protection and modifies the expression of α4β1 and LFA‐1 on T and B lymphocytes in mouse meningitis model

Abstract: The aims of this work were to evaluate the protective role of the 250-kDa polypeptide band of Naegleria fowleri. We designed an immunization strategy in Balb/c mice which were inoculated by i.n. route with an electrocuted 250-kDa polypeptide band of N. fowleri. We observed that the 250-kDa band induced 80% of protection, whereas the coadministration with Cholera Toxin induced 100% of protection. Moreover, high levels of IgA-and IgG-specific antibodies were detected by ELISA assay. We also analysed migration mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition, when mice were immunized with total extract of N. fowleri alone or coadministered with CT, an increment of the levels of IgG and IgA antibodies were detected in serum, nasal washes, and in the nasal cavity of mice. Furthermore, some important antigens of N. fowleri have been found highly immunogenic as the response of IgG and IgA is directed strongly towards some N. fowleri polypeptide bands (Carrasco-Yepez et al 2013;Castillo-Ramírez et al 2021;Cervantes-Sandoval et al 2010;Gutiérrez-Sánchez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when mice were immunized with total extract of N. fowleri alone or coadministered with CT, an increment of the levels of IgG and IgA antibodies were detected in serum, nasal washes, and in the nasal cavity of mice. Furthermore, some important antigens of N. fowleri have been found highly immunogenic as the response of IgG and IgA is directed strongly towards some N. fowleri polypeptide bands (Carrasco-Yepez et al 2013;Castillo-Ramírez et al 2021;Cervantes-Sandoval et al 2010;Gutiérrez-Sánchez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe some characteristics that have been attributed to this protein band. The 250-kDa band has been considered with mucinolytic activity and capable of degrading collagen (Chávez-Munguía et al 2014 ; Martínez-Castillo et al 2016 ); in addition, immunogenic properties have been attributed to this polypeptide band capable to provide 80% protection in mice immunized and challenged with lethal dose of N. fowleri trophozoites (Castillo-Ramírez et al 2021 ; Rojas-Hernández et al 2020 ). The fact that our antibody recognized different bands does not represent the lack of specificity of our antibody.…”
Section: Discussionmentioning
confidence: 99%
“…After conducting a series of in vitro studies, the most promising compounds against N. fowleri should be tested in vivo to proceed further with the lead development process. Several studies have reported animal models of the parasite [ 35 , 36 ], which can be considered by researchers working on anti-Naegleria drug discovery.…”
Section: Discussionmentioning
confidence: 99%